2021
DOI: 10.3390/foods10040796
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pH, Temperature and Protease Inhibitors on Kinetics and Mechanism of Thermally Induced Aggregation of Potato Proteins

Abstract: Understanding aggregation in food protein systems is essential to control processes ranging from the stabilization of colloidal dispersions to the formation of macroscopic gels. Patatin rich potato protein isolates (PPI) have promising techno-functionality as alternatives to established proteins from egg white or milk. In this work, the influence of pH and temperature on the kinetics of PPI denaturation and aggregation was investigated as an option for targeted functionalization. At a slightly acidic pH, rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…This would imply the extensive unfolding and exposure of non-polar moieties of the proteins, and make the proteins more prone to accessing the hydrolytic enzymes during digestion. Previous work has reported a denaturation temperature for patatin of 60.8 • C, while trypsin inhibitor gelation is induced after 70 • C [24,27]. In the present work, a denaturation peak for the commercial potato protein isolate was 68.7 ± 0.28, measured using differential scanning calorimetry (data not shown).…”
Section: Microstructural Characterizationsupporting
confidence: 47%
See 1 more Smart Citation
“…This would imply the extensive unfolding and exposure of non-polar moieties of the proteins, and make the proteins more prone to accessing the hydrolytic enzymes during digestion. Previous work has reported a denaturation temperature for patatin of 60.8 • C, while trypsin inhibitor gelation is induced after 70 • C [24,27]. In the present work, a denaturation peak for the commercial potato protein isolate was 68.7 ± 0.28, measured using differential scanning calorimetry (data not shown).…”
Section: Microstructural Characterizationsupporting
confidence: 47%
“…At the acidic pH of the gastric stages G1 and G3 (pH 5.5-3.6, Figure 2b,c), the protein suspensions were characterized by the presence of interacting particles, and at G3 there seemed to be a semi-continuous matrix, which could be attributed to the formation of an acid-induced network structure. It is indeed reported that protein-protein interactions occur as the surface charge of proteins get closer to their isoelectric point (4.5-5.1), leading to aggregation of the globular patatin [24]. At the final stage of in vitro gastric digestion (Figure 2d) at pH 2.0 (G5), the network is no longer visible.…”
Section: Microstructural Characterizationmentioning
confidence: 87%
“…Hydrophobicity of the Particle Surface. The exposed surface hydrophobicity was determined by fluorescence spectroscopy (Tecan Group Ltd., Mannedorf, Switzerland) using a 1.41 mM N,Ndimethyl-6-propionyl-2-naphthylamine (PRODAN) solution dissolved in methanol, as described by Andlinger et al 20 In brief, the native β-Lg and heat-induced β-Lg particles were diluted to 1 g L −1 using a 100 mM phosphate buffer pH 7. Amounts of 0, 5, 10, 15, 20, 25, 30, 40, and 50 μL of the PRODAN solution were added to each 1000 μL of the diluted solution.…”
Section: Methodsmentioning
confidence: 99%
“…An increase in the NaCl concentration additionally increased the particle size while surface hydrophobicity decreased. Concluding from many studies, ,, a specific combination of pH and salt concentration during thermal-induced particulation allows the particle properties to be controlled in terms of size, reactivity of the free thiol group, and surface hydrophobicity. A change in the pH following particulation allows the zeta potential to be changed subsequently .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it does not form covalently cross-linked elastic gels . The main aggregation and gelation mechanisms are found to be dominated by hydrophobic interactions . Hydrophobic interactions are less specific than covalent bonds and led to different gel structures.…”
Section: Introductionmentioning
confidence: 98%